Efeitos da substituição com íons lantanídeos (Er3+, Tm3+ e Yb3+) nas propriedades de fluorescência da matriz ortoniobato de ítrio (YNbO4) para aplicações em leds de luz branca e sensores ópticos de temperatura - Carmo, Felipe Felix do (2021)
In the present work, polycrystalline fluorescent materials were synthesized from the yttrium orthoniobate (YNbO 4 ) host con taining the lanthanide ions Er 3+3+, Tm 3+ and Yb 3+ by solid state route. X ray diffraction, Raman spectroscopy, and FE SEM were emp loyed for characterization of the samples. X ray diffraction and Raman spectroscopy showed that the substitution with the Er 3+3+, Tm 3+ and Yb 3+ ions was effective for the insertion of these ions i n the sites belonging to the Y 3+ ion. Despite the high substit ution of the host matrix, no important structural changes were observed. This fact was attributed to the similarity in valence and ionic radius of the earth rare ions. The FE SEM micrographs of the pure and doped samples showed no variation in morphology a nd grain size as a function of substitution . The synthesized tri doped phosphors were excited at two wavelengths, 808 and 980nm, and their emissions were analyzed in the visible region. The YNbO 4 : Er 3+3+/Tm 3+3+/Yb 3+ phosphors presented red, green and blue emis sion s at 808 and 980 nm. Emissions relative to blue at 478 nm were attributed to the 1 G 4 3 H 6 transition of the Tm 3+ ion. The emissions related to green at 534 and 555 nm were attributed the transitions 2 H 11/ 2 4 I 15/ 2 and 4 S 3/ 2 4 I 15/ 2 of the Er 3 ion. The re d emission was shown to be formed by contributions from the transitions of the activating ions Tm 3 and Er 3 ++, but the spectral profile of this region showed a greater contribution of the transition 4 F 9/ 2 4 I 15/ 2 related to the Er 3 ion. The transitions 1 G 4 3 H 6 (Tm 3 ++) and 4 F 9/ 2 4 I 15/ 2 (Er 3 + +) were shown to be filled by an energy transfer mechanism (ETU) with 3 and 2 photons, respectively. The 2 H 11/ 2 4 S 3/ 2 4 I 15/ 2 transitions were shown to be filled by a two photon mechanis m at 980 nm and an unusual three pho ton mechanism at 808nm. The increase in the concentration of Tm 3 reduced the emissions related to blue and green due to the possible energy transfer processes Tm 3 Tm 3+ and Er 3 Tm 3 ++, respectively. The white light emission with chromatic coordinates x = 0 .31 and y = 0.35 was obtained in the composition YNO: 0.5% Er 3 2.0% Tm 3 20% Yb 3 under 64.5mW/ cm 2 at 980 nm and x = 0.35; y = 0.36 in composition YNO: 0.5% Er 3 2.0% Tm 3 15 % Yb 3 under 12.0 W/ cm 2 at 808nm The temperature dependent luminescence is inves tigated under 980 nm excitation, and YNETY 05 2 20 sample showed five correlations between pairs of emission bands, two correlations between thermally coupled levels, and three correlations of non thermally coupled levels. The pair of non thermally coupled levels 3 F 2 4 S 3/2 , showed the highest maximum sensitivity of 9,05 10 2 K 1 at 500K with a relative sensitivity of 0.67% K 1 , a promising value when compared to other works published in the literature. The chromatic coordinates of the YNETY 05 2 20 sample c hanged with increasing temperature, with decreasing intensities in the blue and green regions and increasing in the red region of the with decreasing intensities in the blue and green regions and increasing in the red region of the visible spectrum, subtly shifting the chromatic coordinates towards the red regivisible spectrum, subtly shifting the chromatic coordinates towards the red region of the CIE on of the CIE graphgraph.. Keywords: